2007
DOI: 10.1007/s00439-007-0397-0
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variants in the genes for the interleukin-23 receptor (IL23R) and its ligand (IL12B) confer protection against psoriasis

Abstract: Psoriasis is an inflammatory skin disorder that is inherited as a multifactorial trait. Genetic analyses have repeatedly identified a primary disease susceptibility locus lying within the major histocompatibility complex (MHC), on chromosome 6p21. A small number of non-MHC susceptibility loci have also been identified. These regions tend to overlap with susceptibility intervals for Crohn's disease and atopic dermatitis, suggesting the possibility that genetic variants affecting inflammatory pathways may contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
246
4
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(276 citation statements)
references
References 29 publications
15
246
4
11
Order By: Relevance
“…[7][8][9] Recently, we have reported psoriasis-associated diplotypes at IL12B, confirming and extending the previous work by Tsunemi et al, 10 and predisposing/protective diplotypes at IL23R using a multi-staged, case-control design, scanning 25 215 genecentric single nucleotide polymorphisms (SNPs). 11 These results have been verified in four independent studies [12][13][14][15] and have paralleled association studies in related diseases. One of the IL23R missense SNPs implicated in psoriasis, R381Q, has also been strongly associated with several autoinflammatory phenotypes: several studies have found R381Q-mediated predisposition to adult inflammatory bowel disease (IBD), especially Crohn's disease [16][17][18][19][20][21] and pediatric Crohn's disease in individuals of European descent, [22][23][24] two sizable studies reported association of multiple IL23R SNPs with ankylosing spondylitis (AS) 25,26 and a North American study demonstrated IL23R susceptibility for Graves' ophthalmopathy (GO).…”
Section: Introductionsupporting
confidence: 60%
“…[7][8][9] Recently, we have reported psoriasis-associated diplotypes at IL12B, confirming and extending the previous work by Tsunemi et al, 10 and predisposing/protective diplotypes at IL23R using a multi-staged, case-control design, scanning 25 215 genecentric single nucleotide polymorphisms (SNPs). 11 These results have been verified in four independent studies [12][13][14][15] and have paralleled association studies in related diseases. One of the IL23R missense SNPs implicated in psoriasis, R381Q, has also been strongly associated with several autoinflammatory phenotypes: several studies have found R381Q-mediated predisposition to adult inflammatory bowel disease (IBD), especially Crohn's disease [16][17][18][19][20][21] and pediatric Crohn's disease in individuals of European descent, [22][23][24] two sizable studies reported association of multiple IL23R SNPs with ankylosing spondylitis (AS) 25,26 and a North American study demonstrated IL23R susceptibility for Graves' ophthalmopathy (GO).…”
Section: Introductionsupporting
confidence: 60%
“…2 Genome-wide linkage scans have unambiguously mapped a primary disease susceptibility locus (PSORS1) to the major histocompatibility complex (MHC), 3 where refinement studies and resequencing efforts point to HLA-C as the most likely PSORS1 candidate. 4,5 More recently, the advent of genome-wide association scans has allowed the identification of several non-MHC susceptibility genes, including IL12B, IL23R, RNF114, TNFAIP3, TNIP1, IL4/IL13 and LCE3B/3C [6][7][8][9][10][11] Of these, IL12B and IL23R harbour variants that also confer susceptibility to Crohn's disease (CD) 12 and ankylosing spondylitis. 13 Similarly, TNFAIP3 alleles have been associated with rheumatoid arthritis, 14 systemic lupus erythematosus 15 and type I diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of all these loci is not yet understood, but the recent finding that polymorphisms in the interleukin 23 receptor and its ligand interleukin 12 influence susceptibility to psoriasis reflects evidence that biological therapy directed against these cytokines is effective. 14,15 In the case of atopic eczema, a predisposition locus at the epidermal differentiation complex is due at least in part to common null mutations in the gene encoding the epidermal barrier protein filaggrin. 16 Ten per cent of European subjects carry such mutations, which in the homozygous state cause ichthyosis vulgaris.…”
Section: Complex Traits: Inflammatory Skin Diseasementioning
confidence: 99%